(untitled) (Journal of Comparative & International Higher Education, 2024)
Canada has a long history of digital and online learning. The article gives a brief overview of the development of digitalization of teaching and learning in Canadian HE, and the current status in terms of online and blended enrolments across the country, including the impact of Covid-19. The main reasons for this shift in teaching and learning are discussed, as well as the main challenges and opportunities Canadian HE institutions face as a result of the digitalization of teaching and learning. The article ends with conclusions about the extent and type of digitalization, its objectives, and the attitudes and policies of the main stakeholders towards digitalization of teaching and learning in Canadian HE institutions.